The Influence of Social Media Marketing and Influencers on Purchase Decisions of Culinary MSMEs in Bandung Regency - Salsabila, Nabilah; Sumawidjaja, Riyandi Nur (International Journal of Marketing & Human Resource Research, 2025)
Purchase decision is a crucial concept in marketing because various elements that support or hinder a purchase decision significantly affect the choice to acquire a good or service. One element that affects the purcahse decision is social media marketing and influencers. This research was carried out to understand the extent of the impact of marketing through social media and influencers on purchase decisions. This research method implements qualitative and quantitative analysis using questionnaire data collection techniques. Sampling was done by probability sampling with simple random sampling involving 100 respondents. To analyze the data to answer the research question, validity and reliability tests, descriptive analysis, classical assumption testing, multiple linear regression, and hypothesis testing both partially and simultaneously were used. The results showed that (1) every aspect of the purchase decision received a positive rating in the good category. (2) respondents also gave a good rating on social media marketing in all questions (3) for influencers; they scored good on 4 and a fair rating on 2. (4) Social media marketing positively influences individual purchasing decisions. (5) Influencers positively impact purchase decisions (6) Simultaneously, social media marketing and influencers show a positive and significant influence on purchase decisions. That way, if the marketing strategy on social media and the use of influencers in promotions in the MSME culinary sector are more effective, then it will affect the level of consumer purchase decisions for MSME culinary.